Risk Perception and Depression in Public Health Crises: Evidence from the COVID-19 Crisis in China - Ding, Yubin; Xu, Junling; Huang, Sisi; Li, Peipei; Lu, Cuizhen; Xie, Shenghua (International journal of environmental research and public health, 2020)
Background: Scant attention has been paid to how risk perceptions of public health crises may affect people’s mental health. Aims: The aims of this study are to (1) construct a conceptual framework for risk perception and depression of people in public health crises, (2) examine how the mental health of people in the crisis of Coronavirus Disease 2019 (COVID-19) is affected by risk perception and its associated factors, including distance perception of the crisis and support of prevention and control policies, and (3) propose policy recommendations on how to deal with psychological problems in the current COVID-19 crisis. Methods: Online questionnaire survey was implemented. A total of 6373 people visited the questionnaire online, 1115 people completed the questionnaire, and the number of valid questionnaires was 1081. Structural equation modeling was employed for data analysis. Results: Risk perception and its associated factors significantly affect the mental health of people in public health crises. Specifically, (1) distance perception of public health crises is negatively associated with depression among people, (2) affective risk perception is positively associated with depression of people in public health crises, (3) cognitive risk perception is negatively associated with depression of people in public health crises, and (4) support of prevention and control policies is negatively associated with depression of people in public health crises. Conclusion: The findings of this study suggest that risk perception plays an important role in affecting the mental health of people in a public health crisis. Therefore, health policies aiming to improve the psychological wellbeing of the people in a public health crisis should take risk perception into consideration.